Extracting static elastic moduli of rock through elastic wave velocities - Zhang, Yuliang; Gu, Yiming; Zhou, Hongtu; Yang, Lining (Acta geophysica, 2024)
In many geological conditions, obtaining the static elastic moduli of crustal rocks is an essential subject for accurate mechanical analyses of crust. The elastic wave method may be the best choice if rock specimens cannot be taken since elastic wave propagation can be applied to in-situ environments. Although many signs of progress have been made in the elastic wave method, some issues still restrict the accurate extraction of static moduli and its applications. A review of this method and its further research prospect is urgently needed. With this purpose, this paper summarized and analyzed the published experimental data about the relationship between the static and dynamic Young’s moduli of rock, and the frequency dependence of wave velocities and dynamic elastic moduli. P- and S-wave velocities, Young’s, and bulk moduli of rock, especially the saturated rock, have strong frequency dependence in a wide frequency range of 10 –6 –10 6 Hz. Different rocks or conditions (such as water content, amplitude, and pressure), have different frequency-dependent characteristics. The current elastic wave method can be classified into two methods: the empirical correlation method and the multifrequency ultrasonic method. The basic principle, advantages, and disadvantages of both methods are analyzed. Especially, the reasonability of the multifrequency ultrasonic method was elaborated given the nonlinear elasticity, strain level/rate, and pores/cracks in rock materials. Existing problems and prospects on the two methods are also pointed out, such as the choice of a proper empirical correlation, accurate determination of the critical P- and S-wave velocities, the prediction of Young’s modulus at each strain level, and the reasonability of the method under various water contents and fracture structures.